The Influence of Instructional Leadership, Work Motivation, and Teacher Well-Being on Teacher Professionalism in Public Elementary Schools - Ilman Nafia; Endang Wuryandini; I Made Sudana (Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri Kerinci, 2025)
This research examines the relationships among instructional leadership, work motivation, and teacher well-being, and their effects on teacher professionalism. Quantitative research was conducted, and data were gathered through questionnaires. The population for this study comprises 116 teachers from State Elementary Schools in the Gajah Mada and Diponegoro clusters, and a total sampling technique was used, with all 116 teachers included. Data analysis involved descriptive analysis and prerequisite tests; the research hypotheses were tested using regression analysis in IBM SPSS Statistics 26. These research findings indicate that instructional leadership positively and significantly influences teacher professionalism, contributing 43,0%. The regression model is Y = 71,327 + 0,761X1, and the F-count = 85,902 > F-table = 3,924. Work motivation positively and significantly influences teacher professionalism, accounting for 33,9% of the contribution. The regression model is Y = 84,881 + 0,622X2, and the F-count = 58,397 > F-table=3,924. A positive and significant influence was also found between teacher well-being and teacher professionalism, with a contribution of 38,2%. The regression model is Y = 80,191 + 0,561X3, and the F-count = 70,458 > F-table= 3,924. Simultaneously, instructional leadership, work motivation, and teacher well-being positively and significantly influence teacher professionalism, contributing 53,9%. The multiple regression model is Y = 50,406 + 0,430X1 + 0,285X2 + 0,207X3, and the F-count = 43.607 > F-table = 1.981.